La sécurité des produits de consommation et le libre-échange - L’Heureux, Nicole (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The Free Trade Agreement between Canada and United States mainly seeks to encourage the exchange of manufactured goods. Consumer protection requirements are not, however, taken into consideration. Nonetheless, judicial, bureaucratic and legislative actions adopted in both countries for the security of goods such as mandatory information, product bans, mandatory product standarization requirements, mandatory design, and performance standards, judicial awards of compensation in product liability suits etc. may affect the concurential position of exporters and influence the substance of domestic consumer protection laws. It is the author's objective to measure the impact that different domestic regulations may have on the security of products within the framework of the Free Trade Agreement. In the first part of this paper, the author explores American legislation on the security of products and compares it with Canadian legislation. In the second part, the author considers the liability of manufacturers and evaluates the impact of the statutory regulation on their liability for dangerous products in each country.